Methods for measuring women's empowerment - Doss, Cheryl R.; Malapit, Hazel J.; Comstock, Andrew R. (International Food Policy Research Institute, 2020)
Women’s empowerment is of paramount importance for multiple development goals. However, it is much easier to discuss the importance of empowerment than it is to define the methods and tools needed to measure it. This requires research focused on the conceptual understanding of how we should measure women’s empowerment, in a variety of facets, and the creation of tools and methods for doing so.